Immunohistochemical features of ovarian structure at polycystic ovary syndrom depending on the age - I. Yu. Ganzhiy (Patologìâ)
peculiarities of proliferation factors and androgens receptors expression in women with PCOS, depending on age were analyzed. It was revealed that pronounced expression of PCNA, cytokeratin and androgen receptors in stroma and intengification of PCNA expression inereasewith age. Carcinoembryonic antigen and Ki-67 were not found in any woman. polycystic ovary syndrom; PCNA; Ki-67; proliferation; androgen receptors